Improvement of long-term survival by cardiac contractility modulation in heart failure patients: A case–control study. (1st March 2016) - Liu, Ming; Fang, Fang; Luo, Xiu Xia; Shlomo, Ben-Haim; Burkhoff, Daniel; Chan, Joseph Y.S.; Chan, Chin-Pang; Cheung, Lili; Rousso, Benny; Gutterman, David; Yu, Cheuk-Man
Abstract: Introduction: Cardiac contractility modulation (CCM) has been shown to be effective in improving symptoms and cardiac function in heart failure (HF). However, there is limited data on the role of CCM on long-term survival, which was explored in the present study. Methodology: Forty-one consecutive HF patients with left ventricular ejection fraction (EF) < 40% received CCM and were followed for approximately 6 years. They were compared with another 41 HF patients who were enrolled into the HF registry in the same period, and had similar age, gender, EF and etiology of HF. The primary end-point was all cause-mortality. This was stratified by EF. Secondary end-points included HF hospitalization, cardiovascular death, and the composite outcome of death or heart failure hospitalization. Results: The CCM and control groups were well balanced for demographic data, medications and baseline left ventricular EF (27 ± 6 vs 27 ± 7%, p = NS). The mean follow-up duration was 75 ± 19 months in the CCM group and 69 ± 17 months in the control group. All-cause mortality was lower in the CCM group than the control group (39% vs. 71%, respectively; Log-rank χ 2 = 11.23, p = 0.001). Of note, the improvement of all-cause mortality is more dramatic in patients with EF ≥ 25–40% (36% vs. 80%, Log-rank χ 2 = 15.8, p < 0.001) than those with EF < 25% (50% vs. 56%, p = NS), CCM vs. control respectively. Similar results were shown for the benefit of CCM in the secondary endpoints of cardiovascular death, and the composite outcome of death or heart failure hospitalization. The occurrence of HF hospitalization showed no significant difference between CCM and control groups in the whole cohort (41% vs. 49%, p = NS), but was significantly lower with CCM in subjects with EF ≥ 25–40% at baseline (36% vs. 64%, Log-rank χ 2 = 7.79, p = 0.005). Conclusion: CCM resulted in significant improvement of long-term survival, in particular in those with EF ≥ 25–40%. A reduction in heart failure hospitalizations was also seen in this group of patients with less severely reduced EF.